Gypsum-hosted endolithic communities of the Lake St. Martin impact structure, Manitoba, Canada: spectroscopic detectability and implications for Mars. Issue 4 (18th September 2014) - Rhind, T.; Ronholm, J.; Berg, B.; Mann, P.; Applin, D.; Stromberg, J.; Sharma, R.; Whyte, L.G.; Cloutis, E.A.
Abstract: There is increasing evidence that Mars may have once been a habitable environment. Gypsum is targeted in the search for Martian biosignatures because it can host extensive cryptoendolithic communities in extreme terrestrial environments and is widespread on Mars. In this study the viability of using different spectroscopy-based techniques to identify the presence of gypsum endolithic communities was investigated by analysing various cryptoendoliths collected from the Lake St. Martin impact crater (LSM), a Mars analogue site found in Manitoba, Canada. Concurrently, the cryptoendolithic microbial community structure present was also analysed to aid in assigning spectroscopic features to microbial community members. Two main morphologies of endolithic communities were collected from gypsum deposits at LSM: true cryptoendolithic communities and annular deposits on partially buried boulders and cobbles <1 cm below the soil surface. Endolithic communities were found to be visibly present only in gypsum with a high degree of translucency and could occur as deep as 3 cm below the exterior surface. The bacterial community was dominated by a phylum ( Chloroflexi ) that has not been previously observed in gypsum endoliths. The exterior surfaces of gypsum boulders and cobbles are devoid of spectroscopic features attributable to organic molecules and detectable by reflectance, Raman, or ultraviolet-induced fluorescence spectroscopies. However, exposed interior surfaces show unique endolithic signatures detectable by each spectroscopic technique. This indicates that cryptoendolithic communities can be detected via spectroscopy-based techniques, provided they are either partially or fully exposed and enough photon–target interactions occur to enable detection.